MINAT PEMAIN DALAM MENGIKUTI LATIHAN BOLAVOLI DI KLUB ARLES SAROLANGUN - Mutmaina Mutmaina; Muhammad Supriyadi; Ever Sovensi ($$8@@&&$%K, 2022)
This study aims to determine the interest of players in participating in volleyball training at the Arles Sarolangun club. The research method used is a survey. The sample is 39 players, the sampling technique uses total sampling. Data collection techniques in this study used a questionnaire of 39 questionnaire. Consists of 2 competencies, namely internal and external. Based on the results of the analysis, the conclusion of this research is the interest of players in participating in volleyball training at the Arles Sarolangun Club. Respondents' research on volleyball training factors based on internal factors was 84.27%. Respondents' research on volleyball training factors based on external factors was 76.33%. So research on the interest of players in participating in volleyball training is 78.98%, so that the interest of players in participating in volleyball training can be categorized as High.